(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aims to know attitudes and environmental knowledge of Damascus University students. The sample consisted of (512) male and female, and detected the differences between them according to the variables: sex, discipline of the study( science disciplines/ theoretical disciplines), studying stage( junior/ senior) classes, their preferences of literary and media devices, economic level of the family, and the kind of parents job. The researcher modified the scale of attitudes and ecological knowledge (Maloney, Ward & Braucht, 1975) into local environment, which consists of four subscales ( verbal commitment, actual commitment, emotion, and knowledge). The most important results were : the females were more verbal commitment and emotionally with the environment than males, the senior classes students were more emotional than junior classes. The students of low family economic level had more environmental knowledge than those of high level one. There was a significant positive effect of internet and reading books on environment knowledge of the students. Finally there wasn`t a significant effect of the kind of parents’ job on students environmental attitudes and knowledge.